2003
DOI: 10.3354/dao054097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between white spot syndrome virus and indicators of quality in Penaeus monodon postlarvae in Karnataka, India

Abstract: White spot disease (WSD) is a viral disease of shrimp caused by white spot syndrome virus (WSSV). Stocking WSSV-infected seed has been implicated as a major risk factor for outbreaks of WSD. In addition, the quality of postlarvae batches has been proposed as a predictor for good crops. This paper describes the relationship between indicators of quality and WSSV in postlarvae (PL) of Penaeus monodon from Karnataka, India, over the period September 1999 to January 2000. Three outcome variables were considered: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The descriptive and probit regression analysis revealed that stocking screened PL alone cannot guarantee protection against WSSV. A study carried out in India also draws similar conclusions (Corsin, Thakur, Padiyar, Madhusudhan, Turnbull, Mohan, Hao & Morgan ). This supports the project's philosophy that thorough preparation of the gher and maintenance of bio‐security [Bio‐security is the protection of living organisms by the exclusion of pathogens and other undesirables.…”
Section: Summary and Discussion Of The Main Findingssupporting
confidence: 64%
“…The descriptive and probit regression analysis revealed that stocking screened PL alone cannot guarantee protection against WSSV. A study carried out in India also draws similar conclusions (Corsin, Thakur, Padiyar, Madhusudhan, Turnbull, Mohan, Hao & Morgan ). This supports the project's philosophy that thorough preparation of the gher and maintenance of bio‐security [Bio‐security is the protection of living organisms by the exclusion of pathogens and other undesirables.…”
Section: Summary and Discussion Of The Main Findingssupporting
confidence: 64%
“…Corsin et al (2003) indicated that, in Karnataka, India, potential risk factors for WSSV included improper salinity in transportation bags, improper post-larvae (PL) length, and late stocking date. However, very little information is available about risk factors at the pond or farm level.…”
mentioning
confidence: 99%
“…The mechanism for WSSV inhibition at 32°C has recently been discovered (Lin et al, 2011). However, use of such methods to improve post larval quality without also providing appropriate biosecurity in rearing ponds (e.g., carrier removal and restricted water exchange) does not significantly reduce the incidence of disease outbreaks in areas where WSSV may be prevalent in natural carriers and exchange water (Corsin et al, 2002(Corsin et al, , 2003.…”
Section: Major Viral Pathogens Of P Monodon In Asiamentioning
confidence: 98%